Improved immunogenicity of high-dose influenza vaccine compared to standard-dose influenza vaccine in adult oncology patients younger than 65 years receiving chemotherapy: A pilot randomized clinical trial. Issue 4 (27th January 2016) - Jamshed, Saad; Walsh, Edward E.; Dimitroff, Lynda J.; Santelli, Jeanine Seguin; Falsey, Ann R.
Abstract: Purpose: Patients undergoing chemotherapy often fail to develop robust responses to influenza vaccination. Compared to standard-dose influenza vaccine (SD), high-dose influenza vaccine (HD) has shown improved immunogenicity and protection against influenza illness in adults 65 years and older. This study compared the immunogenicity and tolerability of HD to SD in adults younger than 65 years of age receiving chemotherapy. Methods: This double-blind study randomized patients receiving chemotherapy to vaccination with either SD or HD influenza vaccine. Hemagglutination inhibition assays (HAI) were performed prior to and 4 weeks after vaccination. HAI were summarized as geometric mean titers (GMT), seroconversion rates, and seroprotection rates. Results: A total of 105 subjects were enrolled in the trial (51 received SD and 54 received HD). Subjects were well matched for demographic and medical conditions. Both vaccines were well tolerated with no SAEs. Of the 100 subjects with evaluable data, seroconversion rates for all 3 influenza antigens & post-vaccination GMTs for H3N2 & B strains were significantly improved with HD compared to SD. Seroprotection was excellent and equivalent in both groups. Conclusions: Trivalent high-dose influenza vaccine can be safely administered to patients receiving chemotherapy with improved immunogenicity and seroconversion compared to standard-dose vaccine. Post-vaccination seroprotection rates were similar in both groups. A larger study is needed to show clinical benefits with HD in this population. This study was registered at ClinicalTrials.gov asNCT01666782 .